Anfíbios anuros em campos de altitude no sul do Brasil: efeitos do habitat, degradação, sensibilidade e tolerância térmica - Bastiani, Veluma Ialú Molinari de (2023)
The Highland Grasslands of the Atlantic Forest are important ecosystems highly threatened by the advance of agriculture and silviculture, however, historically neglected from the point of view of conservation. Despite this, they are home to several endemic species of amphibians, many recently discovered, so understanding the ecological characteristics and threats to these species is essential to define conservation strategies. Here, we analyze the vulnerability of amphibian species in native and anthropized grassland landscape in a region of Highland Grasslands located on the borders of the states of Paraná and Santa Catarina, in relation to the effects of land use, degradation, sensitivity and thermal tolerance. For this purpose, we: i) describe aspects of the reproductive biology and population size of a microendemic species from Highland Grasslands and endangered, Pithecopus rusticus; ii) we determined the sensitivity and thermal tolerance to warming and cooling in P. rusticus tadpoles and in aquatic predators (dragonfly naiads), to analyzed the potential vulnerability of these organisms in the current and future global warming scenarios; and iii) we evaluated the genotoxicity potential of the environmental matrix (native grassland versus agriculture), quantifying oxidative stress and DNA damage (comet assay) in tadpoles of three anuran species. We collected data in the field and performed experiments in the laboratory, aiming to identify potential threats at the thermal level under controlled conditions, as well as cellular damage. The reproductive activity of P. rusticus occurred from October to January. We recorded a high recapture rate (>50%) in the breeding seasons studied and a low population size. Males and females used the vegetation on the water's edge and spawns were deposited in only two species of herbaceous plants. With the sensitivity and thermal tolerance experiments, we found that P. rusticus tadpoles may be more vulnerable than their predators, dragonfly larvae, in the face of the current scenario of climate change. Furthermore, using three species of wide distribution, we demonstrate that changes in land use can cause irreversible damage to amphibians occurring in the region, especially by contamination of water and soil by pesticides and fertilizers. In this sense, this can be an additional threat to endemic species that are already at risk of extinction. Our data call attention to the urgent need to implement protective measures in grasslands, especially in wetlands, with the aim of preventing the loss of species that are unique to this region.